2017
DOI: 10.2340/00015555-2748
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumour DNA for Monitoring Treatment Response to Anti-PD-1 Immunotherapy in Melanoma Patients

Abstract: Anti-programmed cell death-1 (anti-PD-1) antibody shows high therapeutic efficacy in patients with advanced melanoma. However, assessment of its therapeutic activity can be challenging because of tumour enlargement associated with intratumoural inflammation. Because circulating tumour DNA (ctDNA) correlates with tumour burden, we assessed the value of ctDNA levels as an indicator of tumour changes. Quantification of ctDNA (BRAFmutant or NRASmutant) levels by droplet digital PCR in 5 patients with BRAF or NRAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
1
28
0
Order By: Relevance
“…Another study showed that circulating tumor DNA in the peripheral blood began decreasing between 2 and 4 weeks from the initial administration of Nivo in response cases. 13 In fact, one of the PR patients in this series (case 2) showed a transient increase in serum 5-S-CD from 71.3 nmol/L at baseline to 111.9 nmol/L at 11 days afterwards, which had later decreased to 9.2 nmol/ L at 39 days. Therefore, we presumed that serum 5-S-CD within 3 weeks of Nivo commencement would also be influenced by melanoma onycholysis.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Another study showed that circulating tumor DNA in the peripheral blood began decreasing between 2 and 4 weeks from the initial administration of Nivo in response cases. 13 In fact, one of the PR patients in this series (case 2) showed a transient increase in serum 5-S-CD from 71.3 nmol/L at baseline to 111.9 nmol/L at 11 days afterwards, which had later decreased to 9.2 nmol/ L at 39 days. Therefore, we presumed that serum 5-S-CD within 3 weeks of Nivo commencement would also be influenced by melanoma onycholysis.…”
Section: Discussionmentioning
confidence: 60%
“…In that report, circulating tumor DNA became temporarily elevated within 5 days after starting BRAF inhibitor therapy, probably due to onycholysis. Another study showed that circulating tumor DNA in the peripheral blood began decreasing between 2 and 4 weeks from the initial administration of Nivo in response cases . In fact, one of the PR patients in this series (case 2) showed a transient increase in serum 5‐ S ‐CD from 71.3 nmol/L at baseline to 111.9 nmol/L at 11 days afterwards, which had later decreased to 9.2 nmol/L at 39 days.…”
Section: Discussionmentioning
confidence: 70%
“…Conversely, LDH levels can remain within the normal range despite tumour progression. CtDNA is also a useful marker of tumour load during treatment of patients with melanoma (5,6). Here, we show that measuring ctDNA is a reliable tool for disease monitoring because ctDNA levels reflect tumour burden independently of therapy-related AEs.…”
Section: Discussionmentioning
confidence: 70%
“…Circulating tumour DNA (ctDNA), which is released from tumour cells into the peripheral blood, is a novel biomarker of tumour status (4) as it harbours the same genetic alterations present in the tumour. Also, the amount of ctDNA correlates strongly with tumour burden in cancer patients, including those with melanoma (5). Here, we show that melanoma therapies induced severe AEs, which increase LDH levels, but do not affect ctDNA levels.…”
mentioning
confidence: 53%
See 1 more Smart Citation